2010
DOI: 10.1088/0022-3727/43/9/095002
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of barium hexaferrite film on wide bandgap semiconductor 6H–SiC by molecular beam epitaxy

Abstract: Epitaxial barium ferrite (BaM) films have been successfully grown by molecular beam epitaxy (MBE) for the first time on 6H silicon carbide substrates by using a 10 nm single crystalline MgO (1 1 1)//SiC(0 0 0 1) template, also grown by MBE. X-ray photoelectron spectroscopy showed that the thin MgO template in the early stages of film growth prevented the diffusion of Si into the BaM film. Background oxygen pressure (containing both O atoms and O2, but no ionic species) is critical for determining the chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In 2010, Cai et al demonstrated the MBE growth of both MgO buffer layers and BaM thin films on 6H-SiC substrates. 14 The MgO layers were grown at a substrate temperature of 150 C. For the growth of BaM films, the substrate temperature was set to 800 C.…”
Section: Deposition Of Bam Thin Films On Semiconductor Substratesmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2010, Cai et al demonstrated the MBE growth of both MgO buffer layers and BaM thin films on 6H-SiC substrates. 14 The MgO layers were grown at a substrate temperature of 150 C. For the growth of BaM films, the substrate temperature was set to 800 C.…”
Section: Deposition Of Bam Thin Films On Semiconductor Substratesmentioning
confidence: 99%
“…Emphasis has been placed on the optimization of deposition processes for low-loss, self-biased BaM thin films, 7,8,9,10 the deposition of BaM thin films on "non-conventional" substrates, such as semiconductor substrates 11,12,13,14 and metallic substrates, 15 the fabrication of BaM thick films on semiconductor substrates, 16,17 the demonstration of BaM-based planar mm-wave devices, 18,19,20,21,22,23,10,24 the development of BaM-based ferromagnetic/ferroelectric heterostructures, 25,26,27,28,29 and the study of multiferroic effects in single-phase BaM materials. 30 A variety of different techniques have been used to fabricate BaM film materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 While these properties are important in determining hexaferrites' utility as microwave materials, they also have excellent radiation resistance and high power handling capacities that make them ideal for next-generation microwave devices, especially for use in extreme environments. 8,9 The structure of the hexaferrites is unique in that all the observed structures, including M type, Y type, Z type and so on, are made up of common subunits that are present in different numbers and repeat sequences. 4,10 All subunits are built upon a close packed lattice of oxygen with different metal ion arrangements.…”
mentioning
confidence: 99%